The Development of an Elementary School Teacher Training Program to Improve TPACK Literacy in Indonesia - Ngabiyanto Ngabiyanto; Fonny Dameaty Hutagalung; Ani Rusilowati; Arif Widiyatmoko; Asep Purwo Yudi Utomo; Melissa Salma Darmawan (Universitas Negeri Semarang, 2022)
The major purpose of the study was to develop an elementary school teacher training program to improve TPACK literacy in Indonesia. The method used is ADDIE model (Analyze, Design, Develop, Implementation, and Evaluation). The collected data were analyzed using descriptive and inferential statistics. There are 31 statements related to TPACK literacy including: Pedagogical Knowledge (PK), Content Knowledge (CK), Technological Knowledge (TK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TPK), Technological Content Knowledge (TCK) dan Technological Pedagogical Content Knowledge (TPACK). The results showed that the average of pretest is 67.70% and the average of postest is 71.84%. This result showed that the percentage of elementary school teacher's of TPACK literacy in the posttest is higher than in the pretest. The conclusion of this study is elementary school teacher training program can improve TPACK literacy in Indonesia.